Constructing meaning for online learning: Messages from the field - Dixon, Kathryn; Pelliccione, Lina (Australian Association for Research in Education 'AARE', 2004)
Online learning has been a powerful by-product of the ‘network age’, yet current education practices are still grappling with the most effective way to tap into this valuable resource. This paper reports on a series of investigations which aimed to provide a greater understanding of online learning through the eyes of higher education students in two very distinct courses (undergraduate and postgraduate). The study involved two stages of investigation. Survey instruments were designed specifically for each stage. Stage one focused ultimately on the student’s reactions to online delivery, their rates and depths of participation in this environment, and their levels of engagement in the learning process. The aim of stage two was to identify their prior experience and perceptions of online learning environments. The findings revealed that students are entering the University as technically competent and confident people who expect to utilise technology in their learning environment. Students in both groups indicated that the most important feature of the opportunity to work online was the flexibility this approach allowed in terms of being able to study in their own time and in other environments such as home. They also identified that this mode of delivery enabled them to enhance their learning.